Faktor-faktor yang Mempengaruhi Rendahnya Motivasi Belajar Siswa - Ihsani, Febri Annisa; Nurfarhanah, Nurfarhanah (ALSYS, 2024)
The low motivation to learn varies depending on the goals to be achieved in the learning process at school. The level of motivation can be seen from the attitude of students during teaching and learning activities. Motivation to learn can arise or change influenced by various factors. According to Dimyati & Mudjiono (2002) factors that influence learning motivation include students' ideals or aspirations, individual abilities, personal conditions, student environment, dynamic elements in the learning process, and teacher efforts in teaching. This study aims to describe: 1) Factors that influence students' low motivation to learn in terms of factors: a. students' ideals or aspirations, b. students' abilities, c. students' conditions, d. students' environmental conditions, e. dynamic elements in learning and teaching, f. teachers' efforts in teaching students. The method used in this study is quantitative with a descriptive research type. The research sample was 69 students of SMK Pariwisata Aisyiyah Padang in grades X, XI, and XII who were registered in the 2024/2025 academic year who were selected based on the Total Sampling technique. Data were obtained by distributing research instruments in the form of questionnaires on factors that influence low student learning motivation that have been tested for validity and reliability. Data were processed using the Percentage Technique. The results of this study indicate that: 1) factors that influence low student learning motivation are reviewed from the following factors: a. Student ideals or aspirations: difficulty in determining interests and talents (56.62%), b. Student abilities: difficulty focusing on processing lesson materials (47.83%), c. Student conditions: difficulty attending school due to health problems (44.93%), d. Student environmental conditions: avoid talking to deskmates (39.13%), d. Dynamic elements in learning and teaching: easily distracted by things around them that hinder the ability to focus on lesson materials (46.38%), e. Teacher efforts in teaching students: teachers do not provide good examples in learning discipline (44.93%). The implications of guidance and counseling services that can be provided are information services, individual counseling services and group counseling services.